Pengaruh Suplementasi Fe-Anorganik Terhadap Gambaran Sel Darah Kerapu Cromileptes altivelis Terinfeksi Bakteri Vibrio paraha emolyticus - Setiawati, Mia (JURNAL BIOLOGI INDONESIA, 2007)
The Effect of Anorganic- Iron Supplementation on The Blood Cell of Humpback Grouper Fish (Cromileptes altivelis ) Infected by Kbrio parahaemolyticus This experiment was conducted to find the immunity response of humpback grouper (Chromileptes altivelis) correlated to the anorganic-iron supplement in feed. The blood cell was analyzed as the infection response of F5brioparahaemolyticus. The fish weight 6.9 5 0.22 g/ind. was cultured in 60x40~50cm aquarium and stocked at density 10 ind. / aquarium. After the fish fed by inorganic-iron supplementation at 0,25,50 and 100 mg/ kg for 68 days, then infected by J! parahaemolyticus. The blood cell showed the 50 and 100 mg Felkg inorganic-iron supplement enhanced erythrocytes, hematocrite, hemoglobin, lymphocytes and neutrophil after the 24hand the 72ndh ours infection. Total leucocytes backed to normal after the 7Pd infection and the index of phagocytic was higher with the 100 mg Fe/kg of iron supplementation. 1 Key words: iron (Fe), humpback grouper, feed, bacteria and blood cell.